The Extent of Using Six Sigma Concepts DMAIC Model in the Development of Educational Administrative Processes - Oteer, Rabee (Jordan Journal of Educational Sciences, 2018)
This study aims to identify concepts of Six Sigma DMAIC model in the development of educational processes in the Palestinian Ministry of Education, and to determine the impact of variables of: Gender, Job, qualifications, and experience in the extent of using six sigma concepts in the development of educational administrative processes. A questionnaire consisted of 32 items, divided into 5 areas (Define measure, analyze, improve, and control), was administered after verifying for reliability and validity. The sample consisted of 100 employees. The study used adescriptive survey method. Results showed that scores of define, measure, and control were average, whereas scores of analyze, improve, and the total degree were low. There were significant differences in the extent of using six sigma concepts in the development of educational administrative processes due to gender, in favor of females, and due to the experience in favor of 5-10 years, and above 15. No significant differences were found in terms of jop and qualifications. The study recommended the need to implement a comprehensive system of objective measurements to follow up work of the Ministry of Education